Sustainable campus: solid waste minimisation using vermicomposting - Baki, A. (2020)
A newly constructed Puncak Alam Campus of Universiti Teknologi MARA (UiTM) embarked upon sustainable campus initiatives. One of the initiatives was to incorporate waste reductions into the solid waste management using vermicomposting. Laboratory scale tests were conducted to evaluate the vermicomposting of food waste. The expected outcome of the study was to come up with full scale vermicomposting design. The focus of the study was be the food waste, as it constitutes the highest composition of solid waste from the campus. Earthworms species selected were the Africa Night Crawler (Pudrilus eugeniae) due to its aggressiveness. Two types of bedding (cow dung and sewage sludge) were used due to their availability at site. Food waste reductions were found to be almost 100% after 7 days. The end products of earthworms’ casts were found to have high nutrients contents (N, P, K), thus suitable for use as organic fertiliser. The results of the laboratory scale tests enable improvement to be made to the full scale vermicomposting bin design. This will enable full scale implementation of waste reduction initiative as part of the sustainable campus initiatives.